Functional analysis of RRAS2 pathogenic variants with a Noonan-like phenotype - Iida, Takaya; Igarashi, Arisa; Fukunaga, Kae; Aoki, Taiga; Hidai, Tomomi; Yanagi, Kumiko; Yamamori, Masahiko; Satou, Kazuhito; Go, Hayato; Kosho, Tomoki; Maki, Ryuto; Suzuki, Takashi; et al. (Frontiers in Genetics, 2024)
Introduction: RRAS2, a member of the R-Ras subfamily of Ras-like low-molecular-weight GTPases, is considered to regulate cell proliferation and differentiation via the RAS/MAPK signaling pathway. Seven RRAS2 pathogenic variants have been reported in patients with Noonan syndrome; however, few functional analyses have been conducted. Herein, we report two patients who presented with a Noonan-like phenotype with recurrent and novel RRAS2 pathogenic variants (p.Gly23Val and p.Gly24Glu, respectively) and the results of their functional analysis. Materials and Methods: Wild-type (WT) and mutant RRAS2 genes were transiently expressed in Human Embryonic Kidney293 cells. Expression of RRAS2 and phosphorylation of ERK1/2 were confirmed by Western blotting, and the RAS signaling pathway activity was measured using a reporter assay system with the serum response element-luciferase construct. WT and p.Gly23Val RRAS2 were expressed in Drosophila eye using the glass multiple reporter-Gal4 driver. Mutant mRNA microinjection into zebrafish embryos was performed, and the embryo jaws were observed. Results: No obvious differences in the expression of proteins WT, p.Gly23Val, and p.Gly24Glu were observed. The luciferase reporter assay showed that the activity of p.Gly23Val was 2.45 ± 0.95-fold higher than WT, and p.Gly24Glu was 3.06 ± 1.35-fold higher than WT. For transgenic flies, the p.Gly23Val expression resulted in no adults flies emerging, indicating lethality. For mutant mRNA-injected zebrafish embryos, an oval shape and delayed jaw development were observed compared with WT mRNA-injected embryos. These indicated hyperactivity of the RAS signaling pathway. Discussion: Recurrent and novel RRAS2 variants that we reported showed increased in vitro or in vivo RAS signaling pathway activity because of gain-of-function RRAS2 variants. Clinical features are similar to those previously reported, suggesting that RRAS2 gain-of-function variants cause this disease in patients.